2005
DOI: 10.1017/s0012162205000885
|View full text |Cite
|
Sign up to set email alerts
|

Effect of balance training on muscle activity used in recovery of stability in children with cerebral palsy: a pilot study

Abstract: This study explored possible neural mechanisms that contribute to improvements in balance control produced by reactive balance training in children with cerebral palsy (CP). Six children with CP (four males, two females; mean age 9y 4mo), two with spastic hemiplegia (Gross Motor Function Classification System [GMFCS] level I) and four with spastic diplegia (GMFCS level II,) were given 5 days of intensive training in reactive balance control (100 perturbations per day on a moveable force platform). Surface elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 25 publications
4
46
0
4
Order By: Relevance
“…These time periods are consistent with previous works [19,22]. The response amplitude was reported as a ratio with respect to the background level of activity preceding the perturbation (100 ms) [3].…”
Section: Data Processingsupporting
confidence: 91%
“…These time periods are consistent with previous works [19,22]. The response amplitude was reported as a ratio with respect to the background level of activity preceding the perturbation (100 ms) [3].…”
Section: Data Processingsupporting
confidence: 91%
“…More recent studies showed that the activity of the tibialis anterior muscle reduced when patients with an excessive plantarflexion at initial contact used ankle-foot orthoses [11]. Even short-term intensive balance training improved muscle coordination, but the level of adaptation depended on the severity of the child's disability [12]. These studies also suggested that muscle recruitment in patients with CP may change after an intervention.…”
Section: Introductionmentioning
confidence: 99%
“…RP fits into the theory that the neuromuscular control system must allow for the inherent mechanical properties of inactive muscle fibers to relax in order to control movements with precision and that the motor controller adjusts to changes in resting tension of the muscles [17,33]. Judgments of the importance of clinical changes in relationship to measured changes in GMFM-66 scores are not yet established.…”
Section: Discussionmentioning
confidence: 99%
“…Shumway-Cook et al [16] demonstrated that postural balance recovery and stability was improved following training by mechanical perturbations in children with CP. Woollacott et al [17] suggested that reactive balance training by mechanical perturbations could result in changes in specific neural factors of balance control.…”
Section: Introductionmentioning
confidence: 99%